Mobile Health (mHealth) Interventions to Promote Exclusive Breastfeeding in Low-Income Communities: A Scoping Review - Winarsih Winarsih; Dayat Subekti; Herdini Widyaningpertiwi; Tri Sunarsih; Endah Puji Astuti; Elvika Fit Ari Shanti (Journal of Health Research, 2026)
Background: Exclusive breastfeeding (EBF) is a critical determinant of infant health and survival, yet its prevalence remains suboptimal in low-income communities globally. Barriers such as limited access to lactation support and misinformation continue to challenge EBF promotion efforts in these settings. This review maps and evaluates mHealth interventions that promote exclusive breastfeeding in low-income populations. Methods: This scoping review was conducted following the JBI methodology and reported in accordance with the PRISMA-ScR guidelines. A systematic search of PubMed, Scopus, and Web of Science was conducted for articles published up to July 2025. Eligible studies involved any mHealth-based breastfeeding intervention targeted at low-income mothers, and data were charted using a structured PICO framework. Results: Twenty-four studies met the inclusion criteria, with the majority employing SMS-based interventions, mobile applications, and telelactation support. Most studies reported positive outcomes, including increased EBF rates at 6 weeks to 6 months, improved maternal knowledge, and high app usability and acceptability among users. Interventions involving personalized counseling or peer support through mobile platforms appeared particularly effective. A few studies showed limited impact due to digital literacy, infrastructure barriers, or low engagement levels. The heterogeneity in intervention design and outcome measures limits comparability across studies. Conclusion: mHealth interventions demonstrate promising potential in enhancing exclusive breastfeeding practices among low-income communities. Tailored, culturally sensitive, and user-friendly digital tools, particularly those that include peer or health worker support, can help close the breastfeeding equity gap if scaled and sustained effectively. Keywords: Breastfeeding, Health promotion, Mobile applications, Poverty areas, Telemedicine